Vznik a další vývoj Okresního soudu ve Zlíně - David Kolumber (Právněhistorické studie)
The paper examines the establishment and development of the District Court in Zlín (current Czechia) during the transition from the 19th to the 20th century. The study delves into the concerted efforts to establish a judicial presence in Zlín since 1877, culminating in the court’s activation in 1923, despite geographical and infrastructural challenges. The role of Tomáš Garrigue Masaryk and local civic representatives in overcoming these obstacles is highlighted, demonstrating the intersection of legal reform and civic activism. The analysis employed a rigorous methodological framework, using quantitative and qualitative analyses of primary documents, including archival materials from the District Court of Zlín, to elucidate the strategic manoeuvres and political advocacy that characterised the court’s establishment. By situating the development of Zlín’s judiciary within the larger context of local transformations in the early 20th century, the paper contributes novel insights into the dynamics of legal modernisation, the role of the judiciary in shaping regional identity and self-governance, and the reciprocal relationship between central and local entities in the realm of legal and administrative reform. The study also underscores the adaptability of national legal reforms to the specificities of Zlín’s socio-economic context. It highlights the impact of industrial expansion, particularly the influence of the Bata Company, on local governance and judicial functions. Overall, the paper represents a scholarly contribution to the historiography of Czechoslovak legal history, offering a nuanced understanding of the complexities involved in judicial modernisation and the pivotal role of civic engagement and national figures in this process.